TANGGUNG JAWAB PENGUSAHA TERHADAP WISATAWAN PADA USAHA WISATA TIRTA DI BALI - I Ketut Suparta; Ni Nyoman Triyuni (Politeknik Negeri Bali, 2014)
This study, entitled the responsibility of businessman to tourist on Water tourism business in Bali, this is a research study that examines the normative legal norms lack sharpness contained in article 26, paragraph d and e of Act No. 10 of 2009 and its implementing regulations relating to how responsibility the businessman for tourist on water tourism in Bali and sanctions are given to businessman who neglect their duties. In this study, the approach are statute approah and legal concept analysis approach, then the problem is analyzed with the technique later in systematizing description for further evaluated and given argumentation. From the research and discussion that is done it can be known that the responsibility of businessman to tourist on Water tourism business in Bali include administrative responsibilities, moral and legal. While the sanctions applied to businessman who do not perform their obligations in the form of administrative sanctions and / or civil penalties / criminal, either separately or together.